Gender-specific patterns in patenting and publishing - Rainer Frietsch; Inna Haller; Melanie Vrohlings; Hariolf Grupp (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2008)
Measuring the output of men and women in science and technology has previously been mostly restricted to case studies or small-scale surveys. Based on an analysis of patent and publication databases, this paper applies a methodology to systematically assign the gender to the names of inventors and authors. The method is applied to 14 countries. The results of this investigation reveal substantial differences across coun-tries in terms of women's relative contribution1 to science and technology, with the cen-tral European countries of Germany, Austria and Switzerland all ranking comparatively low in this respect. We also examine trends over time, showing that the data on women's share of publications - unlike the results for patents - hardly increase over time for the already better-performing nations.
urn:nbn:de:0011-n-821745
Keywords: 330; measurement; R&D output; gender equality; gender-specific patenting; gender-specific publishing; Patent; Erfindung; Forschung; Geschlecht; Frauen; Welt